Nicotinamide-based agglomerates of ibuprofen: formulation, solid state characterization and evaluation of tableting performance with in-silico investigation - Prerna Hemant Sidwadkar; Nitin Hindurao Salunkhe; Kailas Krishnat Mali; Vijay Bapu Metkari; Durgesh Paresh Bidye (SpringerOpen, 2023)
Abstract Background The objective of the present investigation was to obtain directly compressible agglomerates of ibuprofen with nicotinamide by a quasi-emulsification solvent diffusion technique. Ibuprofen-nicotinamide agglomerates were prepared by quasi-emulsification solvent diffusion technique using ethanol (good solvent), water (poor solvent), and chloroform (bridging liquid). The prepared agglomerates were characterized by ATR-FTIR, powder X-ray diffraction, differential scanning calorimetry, and scanning electron microscopy and were evaluated for tableting performance and in vitro drug release. To appropriately identify the hydrogen bonding sites, a thorough understanding of the structures of API and coformer is necessary, hence molecular docking approach was implemented to depict the interaction between the proposed coformer and COX-2 protein (PDB Id:4PH9). Results The percent yield of agglomerates was in the range of 85-98 w/w%, and drug content for all batches was in the range of 96-99%. The microphotographs showed irregular circularly shaped agglomerates. ATR-FTIR study showed a strong possibility of hydrogen bonding between ibuprofen and nicotinamide. The crystallinity of ibuprofen was slightly reduced and confirmed by P-XRD and DSC. Crushing strength and friability studies showed good handling qualities of ibuprofen agglomerates. Heckel plot studies showed low mean yield pressure and high tensile strength, indicating excellent compressibility and compactibility of ibuprofen agglomerates. More than 90% drug release was obtained within 60 min in PBS (pH 7.4). The docking studies revealed that nicotinamide individually has -CDOCKER energy 16.8109 where coformer showed 29.0584, which indicates coformer has a better binding affinity to target as compared to nicotinamide individual. Conclusions It can be concluded that the agglomerates improved the dissolution, tableting performance, and solid-state properties of ibuprofen and hence can be useful to improve the therapeutic performance of ibuprofen. Graphic Abstract